Atomic‐Level‐Designed Catalytically Active Palladium Atoms on Ultrathin Gold Nanowires. Issue 7 (7th December 2016) - Liu, Rui; Zhang, Li‐Qiang; Yu, Cun; Sun, Meng‐Tao; Liu, Jing‐Fu; Jiang, Gui‐Bin
Abstract : A Ag monolayer facilitates the deposition of isolated Pd atoms rather than continuous ones on ultrathin Au nanowires. During the hydrogenation of nitrophenol and the electrooxidation of ethanol, these two groups of Pd atoms show distinctive but geometry‐dependent catalytic activity. This new atomic geometry maneuvering strategy is ready for the atomically precise design of nanocatalysts.